Peran Bimbingan Orang Tua Dalam Meningkatkan Pengetahuan Nilai – Nilai Muamalah pada anak – anak: The Role of Parental Guidance in Increasing Knowledge of Muamalah Values in Children - Taufiq Akbar; Muhammad Ali; Anas Djumati (Institut Agama Islam Negeri Fattahul Muluk Papua, 2022)
This study purpose to analyze the role of parental guidance in increasing knowledge of muamalah values ​​in children in Jayawijaya Regency.Parental guidance is a provision of assistance, coaching and also encouragement both physically and psychologically from parents given to children to live life in an effort to overcome every problem faced with the aim of the child achieving his welfare. Understanding or knowledge of muamalah values ​​in children can be interpreted as awareness and initial experience of a child in responding to various things in their environment related to muamalah values ​​which indirectly imprint as information used by a child to live his life.This research is an explanatory research with a quantitative approach and uses 92 respondents. Processing and distribution of data in this study were analyzed using path analysis with the AMOS/Structural Equation Model (SEM) V.22 program.The results showed that the role of parental guidance can increase positively and significantly the knowledge of muamalah values ​​in children (cr = 3.408: p = 0.046).